Democracy and libraries: symbol or symbiosis?. Issue 5 (11th June 2018) - Byrne, Alex
Abstract : Purpose: Libraries are frequently claimed to be essential to the functioning of a democratic society and to be symbols of intellectual freedom. The purpose of this paper is to explore the relationship between libraries, public libraries in particular, and democracy. Design/methodology/approach: Data from the Democracy Index produced by the Economist Intelligence Unit and the International Federation of Library Associations and Institutions World Library Map are analysed to test the claimed symbiotic relationship between libraries and democracy. Findings: The findings confirm that there is an identifiable symbiotic relationship between libraries and democracy as claimed, at least for public libraries, and considers some implications of that finding. Originality/value: First analysis of worldwide data to test this hypothesis.